A Novel N, P, C Cage Complex Formed by Rearrangement of a Tricyclic Phosphirane Complex: On the Importance of Non‐covalent Interactions. Issue 23 (15th April 2014) - Nesterov, Vitaly; Espinosa, Arturo; Schnakenburg, Gregor; Streubel, Rainer
Abstract The reaction of Li/Cl P‐CPh3 phosphinidenoid tungsten(0) complex 2 with dimethylcyanamide afforded tricyclic phosphirane complex 4, an unprecedented rearrangement of which led to the novel N, P, C cage complex 6. On the basis of DFT calculations, formation and intramolecular [3+2] cycloaddition of the transient nitrilium phosphane ylide complex 3 to a phenyl ring of the triphenylmethyl substituent to give 4 is proposed. Furthermore, theoretical evidence for terminal N‐amidinophosphinidene complex 7, formed by [2+1] cycloelimination from 4, is provided, and the role of the electronic structure and non‐covalent interactions of intermediate 7 discussed.